FATTY ACID ANALYSIS OF MARINE MICROALGAE Chlorella Sp. IN MODIFIED MEDIUM USED GAS CRHOMATOGRAPHY-MASS SPECTROMETRY (GC-MS) - Kurnia, Dewi (STIKes Bakti Tunas Husada, 2018)
Microalgae is known as a raw materials of pharmaceutical industry, it contains various chemical compounds such as protein, fatty acid, pigments and vitamins. The compound can be use as a basic ingredient of pharmaceutical also can be use as a treatment or prevention agent such as cancer and high cholesterol. Chlorella sp. is a green microalgae which can be found in Indonesia marine area, it also has a high enough of lipid. Compotition of fatty acid from marine microalgae Chlorella sp that cultivated with modification medium has been analyzed. Microalgae culture cultivated with GM 10% as a medium for 8 days. 51,55 L culture produced a 31,0537 gr dry biomass. 31,0537 gr dry biomass Soxhletation produced about 12,8818% w/w oil rendemen. The results of GC-MS analysis, there are 3 types of fatty acids identified in microalgae Chlorella Sp. The composition are palmitic acid (13,34%), linoleic acid (5,39%) and oleic acid (16,40%). Total fatty acid contained is 35,13%Â Keywords:Chlorella sp, fatty acids, GC-MS.